Monitoring of Corrosion-Induced Degradation in Prestressed Concrete Structure Using Embedded Piezoceramic-Based Transducers - Jiang, Tianyong; Kong, Qingzhao; Peng, Zhong; Wang, Lei; Dai, Lizhao; Feng, Qian; Huo, Linsheng; Song, Gangbing (IEEE sensors journal, 2017)
Corrosion-induced cracking in prestressed concrete elements has been one of the most dominant factors that can cause the deterioration of concrete structures. Since most of the corrosion-induced cracks in their early age are invisible, qualitative and quantitative estimation of the corrosion-induced damage is not applicable before surface cracks can be observed. In this paper, the authors present a stress wave-based active sensing approach using embedded piezoceramic-based transducers to monitor the corrosion-induced degradation in prestressed concrete structures. Two concrete beams each mounted with two corrosion tanks were fabricated; one beam was embedded with a pretensioned strand and the other one with an untensioned strand. Two different corrosion rates were also considered in the accelerated corrosion process to verify the reliability and sensitivity of the approach. The characteristics of the propagating stress wave between a pair of embedded piezoceramic-based transducers were highly influenced by the concrete condition on the wave path. The received signals were analyzed in time domain, frequency domain, and through the wavelet packet-based energy index. Experimental results show that the received signal energy slightly increases in the initial corrosion stage due to the internal expansion pressure caused by the corrosion products. Subsequently, with the occurrence and the development of the corrosion-induced cracks, the energy of the received signal decreases as the corrosion damage develops. When the corrosion process almost completes, the energy of the received signal becomes stable. The experimental results show that the developed piezoceramic-based active sensing approach can monitor the corrosion-induced degradation and estimate the progress of the corrosion process in real time, and has potentials to provide early warning of the initial corrosion occurrence for prestressed concrete structures.